Drying shrinkage of concrete elements. (February 2017) - Vinkler, Marek; Vítek, Jan L.
Abstract : The paper deals with shrinkage of large concrete specimens. The segments of walls were cast with thicknesses of 200 mm, 400 mm and 800 mm. Four sides were sealed in order to simulate the drying of infinite walls of different thicknesses. The elements were equipped with vibrating wire strain gauges to measure strains inside the elements, and strains were recorded for a period of 6 months in vertical as well as in horizontal directions. The wall segments are stored in a laboratory. The relative humidity and temperature of the environment are not controlled, but recorded very closely. Additional tests were performed. The concrete compression strength was measured on cubes and uniaxial shrinkage is measured on standard cylinders using embedded vibrating wire strain gauges. The cylinders are stored in three different environments; in the laboratory and in the rooms with a controlled relative humidity of 65% and 100%, respectively. A comparison of measured shrinkage is provided against various shrinkage models (Model Code 2010, Eurocode 2, Model B3, Model B4, Model B4s and Model ACI209R‐92).